2014
DOI: 10.3109/10715762.2014.955484
|View full text |Cite
|
Sign up to set email alerts
|

Changes in skeletal muscle iron metabolism outpace amyotrophic lateral sclerosis onset in transgenic rats bearing the G93A hmSOD1 gene mutation

Abstract: This study showed that multiple mechanisms may underlie iron accumulation in muscles of ALS transgenic rats, which include changes in blood hepcidin and muscle Fpn1 and increased level of muscle ferritin H. These data suggest that impaired iron metabolism is not a result of changes in motor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 36 publications
4
27
0
Order By: Relevance
“…The activity of catalase was higher in TA from ALS II and ALS III muscles ( Figure C). We have shown previously that progression of the disease was accompanied by no change in soleus (SOL) muscle mass and some decrease in TA . In the present study, we confirmed this observation based on EDL muscle, which is mostly built of white fibres and that is where a significant decrease of its mass was observed in ALS II and ALS III animals ( Figure D).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The activity of catalase was higher in TA from ALS II and ALS III muscles ( Figure C). We have shown previously that progression of the disease was accompanied by no change in soleus (SOL) muscle mass and some decrease in TA . In the present study, we confirmed this observation based on EDL muscle, which is mostly built of white fibres and that is where a significant decrease of its mass was observed in ALS II and ALS III animals ( Figure D).…”
Section: Resultssupporting
confidence: 91%
“…The mechanism of iron transport into a cell is quite well understood; however, the cause of iron accumulation, which is observed in certain tissues, is not known. Most of the cells are able to export iron by ferroportin, and we observed that the level of ferroportin protein significantly decreased during progression of ALS in rats . It is important to note that tissue iron accumulation is associated with several morbidities; however, it is still not clear if the phenomenon is a cause or effect of the disease process .…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…This regulatory feedback loop allows for local control over iron trafficking within the CNS, although the abundance of hepcidin in the brain interstitium suggests that at least some fraction of it is of systemic (likely hepatic) origin119. Low levels of ferroportin have been found in brains of patients with AD120, as well as in rat models of PD121 and ALS122. In a mouse model of MS, reduced expression of ferroportin and intracellular iron overload were specifically found in macrophage-like microglia, but not in astrocytes123.…”
Section: Iron and The Pathophysiology Of Diseasementioning
confidence: 99%
“…In contrast, genetically engineered rats have only recently been developed to model disorders such as Alzheimer's disease [1][2][3], autism [4], Parkinson's disease [5][6][7][8], Huntington's disease [9,10], amyotrophic lateral sclerosis [11,12], and spinocerebellar ataxia [13]. In light of novel methods to manipulate the genome of rats [14][15][16] such as the CRISPR-Cas system [17], there will likely be future increases in the production and use of genetically engineered rats to model a variety of neurological disorders.…”
Section: Introductionmentioning
confidence: 90%